Cantwell, Theresa Squires. Black and white photograph of man and child from Theresa Squires Cantwell's personal photograph collection. - Barrett, Terra (1946)
Theresa and her grandfather, William James Squires "Bill" "Will" (1870-1961), sitting on fence.